EMBA29 academic trip exposes students to global business strategies at DHL, MIDA and INTEL - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
On 12 July 2024, as part of the Global Business Strategy course for final-year MBA students of EMBA29 from UITM Perak, an academic trip was organised to DHL Penang Gateway, MIDA Penang, and Intel Penang. The primary objective of this visit was to expose students to the global business strategies adopted by leading organisations to remain competitive in the international market. Discussions also focused on the issues and challenges faced by companies in expanding their businesses into wider markets. In addition, the programme provided valuable opportunities for students to exchange ideas and knowledge with industry experts, allowing them to gain practical insights into real-world business operations. Indirectly, this initiative also helps to promote Universiti Teknologi MARA (UiTM) at the international level as an institution of excellence in higher education.